The Representation of Linguaculture on Tourist Guides at Sade Village - Rahmatullah, Khairo; Amin, Muhammad; Farmasari, Santi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Language and culture are inseparable aspects of communication, particularly in cultural tourism, where tour guides function as mediators between local communities and international visitors. This study aims to investigate how linguaculture is represented by tour guides in Sade Village, Central Lombok, during their interactions with foreign tourists in English. A qualitative descriptive design was employed. The primary data consisted of English conversations between tour guides and tourists, collected through observation, audio recordings, and field notes. The data were analyzed using the linguaculture framework with translational and ethnographic approaches to identify the representation of local vocabulary and local knowledge. The research finds that the linguacultural manifestations of the tour guides in Sade Village are realized in two aspects. First, there is the incorporation of Sasak vocabulary into English-language interactions. Second, the transfer of material and social local knowledge through “expert talk” strategies to manage gaps in understanding (rich points). With this approach, the tour guides can successfully convey the Sasak philosophical values and cultural identity and turn them into meaningful and educational stories for international tourists.